Mechanochemistry as an emerging tool for the preparation of sustained release urea cocrystals as a nitrogen source. Issue 9 (14th February 2022) - Adassooriya, Nadeesh M.; Mahanta, Sanjeev Pran; Thakuria, Ranjit
Abstract : Poor nitrogen usage efficiency of urea is one of the serious drawbacks that need urgent attention. This highlight focuses on the recent developments in mechanochemical synthesis of urea cocrystals as enhanced efficiency fertilizers. Abstract : As the global community is facing serious challenges such as increasing population and shrinking cultivation land that will raise issues regarding sufficient food demand, a 70–100% expansion in global food production will be an essential step. As nitrogen (N) is an essential nutrient for agriculture and food production, N supply to soil and its management are essential for sustainable soil fertilization and crop production. Urea comprises almost 60% of total global use of all the commercially available solid N fertilizer. However, the nitrogen usage efficiency (NUE) of urea by the crop is approximately 47% owing to losses due to high water solubility and evaporation as ammonia to the environment. In this regard, the development of a urea-based enhanced efficiency fertilizer (EEF) with higher NUE is a worthy task with respect to agricultural economy and environmental perspective. This study specifically focuses on the recent developments on mechanochemical synthesis and physicochemical studies of urea cocrystals (both neutral organic and ionic) as EEF.